FAKTOR-FAKTOR YANG MEMENGARUHI TURNOVER INTENTION KARYAWAN BAGIAN PEMBENIHAN PADA PT PRIMA LARVAE KABUPATEN TANGGAMUS - Kamarga, Hafia; Sayekti, Wuryaningsih Dwi; Syarief, Yuniar Aviati (Jurnal Ilmu-Ilmu Agribisnis, 2019)
This study aims to determine the level of personality, motivation, job satisfaction, organizational commitment, and turnover intention, in addition to know the relation between individual characteristics with the turnover intention as well as the influence of personality, motivation, job satisfaction, and organizational commitment on the turnover intention of hatchery employees at PT Prima Larvae. The research use census method and the location is chosen purposively in PT Prima Larvae, located in Cukuh Balak Sub District, Tanggamus Regency. Respondents in this study were all hatchery employees at PT Prima Larvae. Data collection was carried out from October to November 2018. The data analysis method used descriptive and verification analysis using multiple regression analysis. The results of this study indicated that the level of motivation and turnover intention in the high category, while the level of job satisfaction in the medium category but tended to be low and the level of personality in the medium category but tended to be high, and the level of organizational commitment in the low category. The individual characteristics (age and tenure) related to employee’s intention turnover, but not of the level of education and status marital. In overall, personality, motivation, job satisfaction, and organizational commitment influenced on employee turnover while partially only job satisfaction and organizational commitment.Key words: job satisfaction, organizational commitment, turnover intention